Hollywood pride : a celebration of LGBTQ+ representation and perseverance in film - Duralde, Alonso (Running Press, 2024)
"Just in time for Pride Month, this book is a first-of-its-kind in-depth exploration of LGBTQ+ representation from the dawn of cinema through today, from noted film critic Alonso Duralde and Turner Classic Movies"--